Numerical Analysis of Transpiration Cooling in Annular Slinger Combustor. (February 2019) - Zhang, Tao; Feng, Qin; Cai, Wenxiang; He, Wu
Abstract: Wilcox k - ω turbulence model, EBU-Arrhenius turbulence combustion model and six-flux radiation model were applied to simulate turbulence combustion flowfield in a real annular slinger combustor. Structured grids of the annular slinger combustor were generated through TTM method and the anchored grid method. For considering the transpiration holes' cooling effect, reaction flow field in whole annular slinger combustor and in the near-wall region of flame tube were analyzed by numerical simulation, respectively. A new method for data exchanging had been developed to transfer whole flow field numerical result to near-wall region by the inverse distance method, which can solve the contradiction between the requirement of vast computing resources and the computer's processing ability. Wall temperature and cooling effect of flame tube were researched by numerical simulation method, which provides a technological support for the majorization of flame tube's structure.